3D printing method and combination of support bath and eluent
By performing hydrophobic association in support bath materials and using polyethylene glycol eluent, the problem that existing support bath materials cannot adapt to the multi-material properties requirements when manufacturing complex three-dimensional biological tissues and organs is solved, and the effect of enhanced material connection strength and easy elution is achieved.
Patent Information
- Application Number
- CN202210805968.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-16
- Filing Date
- 2022-07-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-07-08
AI Technical Summary
The existing supporting bath materials have problems that multi-material properties cannot be adapted to when manufacturing complex three-dimensional biological tissues and organs, and the biocompatibility and elution are insufficient, making it difficult to meet the manufacturing needs of complex structures.
By hydrophobically associating the polyoxypropylene group with the stearic group in the hydrophobic hydroxypropyl methyl cellulose, an adjustable printing window is formed and polyethylene glycol is used as the eluent to reduce the overall viscosity and facilitate elution.
It realizes a support bath material with good stability and biocompatible, can be printed at lower temperatures and heated to enhance the connection strength of the material in the later stage, and is easy to elute, suitable for multi-material three-dimensional biological tissues and organ manufacturing.
Smart Images

Figure CN115284599B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of biomanufacturing, and more particularly to a 3D printing method and a combination of a support bath and an eluent. Background Art
[0002] As an emerging manufacturing process, suspended biological 3D printing has the potential to manufacture tissues / organs in vitro. It replaces the printing platform from a 2D platform to a 3D support bath, and provides support for the printed structure through the support bath material, reducing the self-supporting strength requirements of the biological ink itself and improving the biological properties of the material. The support bath material has a certain yield stress. When the print nozzle passes through, the shear stress applied by the nozzle exceeds its yield stress, causing it to undergo local shear thinning and liquefy, allowing the biological ink to flow out of the nozzle. After the nozzle leaves, the support bath material exhibits self-healing properties, restores the yield stress, and wraps the extruded material to form a stable structure. In the support bath, biological ink of any shape can be printed in any path. After printing is completed, the biological ink is solidified and the support bath is removed using physical and chemical conditions such as cross-linking agents or light to obtain a biological structure that meets the characteristic morphology requirements. At present, this has been used to manufacture hollow structures, structures with overhanging features, and biological tissue / organ models such as the heart.
[0003] Known support baths have their own defects. For example, the temperature sensitivity of gelatin particles makes it impossible to print temperature-sensitive inks, the ion sensitivity of Kappol particles makes it impossible to print inks based on ion cross-linking, the gellan gum particles are difficult to elute, so the printed structure cannot be extracted, and the poor biocompatibility of lithium ion support baths reduces the cell survival rate in bio-inks. As a result, existing support baths can only be specifically adapted to certain materials and applications. The tissues and organs in the human body are heterogeneous, and each part is composed of materials and cells with different properties. The multi-material property requirements for the manufacture of heterogeneous human tissues are inconsistent with the inability of existing support baths to adapt to the simultaneous construction of multiple materials, making it impossible for existing support bath materials to meet the needs of complex three-dimensional biological tissue and organ manufacturing.
[0004] Application Contents
[0005] The content of this application is used to introduce concepts in a brief form, which will be described in detail in the detailed implementation section below. The content of this application is not intended to identify the key features or essential features of the technical solution claimed for protection, nor is it intended to limit the scope of the technical solution claimed for protection.
[0006] In order to overcome the shortcomings of the existing technology, this study combines the biocompatibility, stability, compatibility with common cross-linking / curing, and hydrophobicity of hydrophobically treated hydroxypropyl methylcellulose and the biocompatibility, easy elution, and hydrophilicity of poloxamer. The polyoxypropylene group is hydrophobically associated with the stearyl group in the hydrophobically treated hydroxypropyl methylcellulose to reduce the high viscosity caused by pure hydrophobically treated hydroxypropyl methylcellulose, and an adjustable printing window is formed by polymerization between polyoxyethylene groups. Polyethylene glycol is used as an eluent, and its strong hydrophilicity and small molecular structure can block between aggregates, reduce the overall viscosity, and facilitate elution. Relying on the support bath, a suspension printing method with enhanced material connection strength and a multi-material printing method are proposed. The suspension printing method with enhanced material connection strength reduces the viscosity of the printed materials by increasing the temperature after printing at a lower temperature, and fuses them with each other to increase the connection strength. The multi-material printing method is to add a cross-linking agent such as calcium chloride and glutamine transferase to the support bath, print one or more materials in it, and cross-link and solidify them in the support bath.
[0007] In order to achieve the above objectives, this application adopts the following technical solutions:
[0008] As a first aspect of the present application, a 3D printing method is provided, comprising the following steps:
[0009] Weigh a phosphate buffered saline solution and / or deionized water and place them in a mixing container, then place the container in a refrigeration device to cool to 4° C., weigh a preset mass of poloxamer and add it to the mixing container, and keep the temperature of the refrigeration device at 4° C. until the poloxamer is completely dissolved;
[0010] The solution after the poloxamer is completely dissolved is heated to 50° C., and a preset mass of hydrophobic-treated hydroxypropyl methylcellulose is gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a support bath material;
[0011] adding additives to the support bath material;
[0012] Performing 3D printing in a mixture of the support bath material and the additive using a 3D printing material;
[0013] After the 3D printing is completed, at least the support bath material is eluted using an eluting liquid.
[0014] Furthermore, the hydrophobic treatment includes: grafting stearyl groups to hydroxypropyl methylcellulose.
[0015] Furthermore, the additive includes one or more of calcium chloride, transglutaminase, sodium hydroxide and calcium hydroxide.
[0016] Furthermore, the 3D printing material includes one or more of sodium alginate, gelatin, methacrylic anhydride gelatin, chitosan, hyaluronic acid, and collagen.
[0017] Furthermore, the eluent includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500, polyethylene glycol 600, and polyethylene glycol 800.
[0018] Furthermore, the supporting bath material comprises, by weight:
[0019] Hydroxypropyl methylcellulose 2 to 4 parts;
[0020] Poloxamer 5 to 15 parts;
[0021] The rest is phosphate buffer solution and / or deionized water.
[0022] Furthermore, the mass percentage of hydroxypropyl methylcellulose in the supporting bath material ranges from 2% to 4%; the mass percentage of poloxamer in the supporting bath material ranges from 5% to 15%.
[0023] Furthermore, the structural formula of the hydrophobically treated hydroxypropyl methylcellulose is:
[0024]
[0025] Furthermore, the structural formula of the poloxamer is:
[0026]
[0027] As a second aspect of the present application, a combination of a support bath and an eluent thereof is provided, wherein the support bath material comprises, in parts by mass:
[0028] Hydroxypropyl methylcellulose 2 to 4 parts;
[0029] Poloxamer 5 to 15 parts;
[0030] The rest is phosphate buffer solution and / or deionized water;
[0031] The eluent includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500, polyethylene glycol 600, and polyethylene glycol 800.
[0032] The benefit of the present application lies in that it provides a 3D printing method for printing using a supporting bath material with good stability, biocompatibility and rheological properties, and a combination of a supporting bath and its eluent. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The drawings constituting a part of this application are used to provide a further understanding of this application, so that other features, purposes and advantages of this application become more obvious. The illustrative embodiment drawings and their descriptions of this application are used to explain this application and do not constitute an improper limitation on this application.
[0034] In addition, throughout the drawings, the same or similar reference numerals represent the same or similar elements. It should be understood that the drawings are schematic and that the components and elements are not necessarily drawn to scale.
[0035] In the attached picture:
[0036] Figure 1 Schematic diagram of the support bath materials hydrophobically treated hydroxypropyl methylcellulose and poloxamer support bath for this application;
[0037] Figure 2 A schematic diagram of a suspension printing method for enhancing the connection strength of supporting bath materials for this application;
[0038] Figure 3 A schematic diagram of a multi-material suspension printing method supporting bath materials for this application;
[0039] Figure 4 (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath prepared in Example 1 of the support bath material of the present application;
[0040] Figure 5 (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 2 of the support bath material of the present application;
[0041] Figure 6 The (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 3 of the support bath material of the present application;
[0042] Figure 7 (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 4 of the support bath material of the present application;
[0043] Figure 8 (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 5 of the support bath material of the present application;
[0044] Fig. 9 (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 6 of the support bath material of the present application;
[0045] Fig.10The (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 7 of the support bath material of the present application;
[0046] Fig.11 The (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 8 of the support bath material of the present application;
[0047] Fig.12 (A) temperature-viscosity diagram, (B) shear stress-shear rate diagram, and (C) viscosity-time diagram of the support bath in Example 9 of the support bath material of the present application;
[0048] Fig.13 This is a temperature-viscosity diagram of the supporting bath in Example 10 of the supporting bath material of the present application;
[0049] Fig.14 The effect diagram (A) and stress-strain curve (B) of the multi-material suspension printing method in Example 11 of the supporting bath material of this application are the maximum strain;
[0050] Fig.15 This is a processing effect diagram of the suspension printing method for enhancing the material connection strength in Example 12 of the supporting bath material of this application. DETAILED DESCRIPTION
[0051] Embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although certain embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present disclosure. It should be understood that the drawings and embodiments of the present disclosure are only for exemplary purposes and are not intended to limit the scope of protection of the present disclosure.
[0052] It should also be noted that, for ease of description, only the parts related to the relevant application are shown in the drawings. In the absence of conflict, the embodiments and features in the embodiments of the present disclosure can be combined with each other.
[0053] It should be noted that the concepts such as "first" and "second" mentioned in the present disclosure are only used to distinguish different devices, modules or units, and are not used to limit the order or interdependence of the functions performed by these devices, modules or units.
[0054] It should be noted that the modifications of "one" and "plurality" mentioned in the present disclosure are illustrative rather than restrictive, and those skilled in the art should understand that unless otherwise clearly indicated in the context, it should be understood as "one or more".
[0055] The names of the messages or information exchanged between multiple devices in the embodiments of the present disclosure are only used for illustrative purposes and are not used to limit the scope of these messages or information.
[0056] The present disclosure will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0057] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used for illustration and are not intended to limit the scope of the present application. In addition, it should be understood that after reading the content taught in the present application, those skilled in the art may make various changes or modifications to the present application, and these equivalent forms also fall within the scope limited by the attached claims of the present application.
[0058] A supporting bath material comprises hydrophobically treated hydroxypropyl methylcellulose and poloxamer; the components are 2-4% of hydrophobically treated hydroxypropyl methylcellulose and 5-15% of poloxamer by weight.
[0059] Among them, hydrophobically treated hydroxypropyl methylcellulose was purchased from Daido Chemical Co., Ltd. of Japan, and poloxamer was purchased from Merck & Co., Ltd. of the United States.
[0060] The support bath material is eluted by reducing the viscosity of the polyethylene glycol eluent, and the component percentage is 2-10%. The polyethylene glycol can be one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500, polyethylene glycol 600, and polyethylene glycol 800. The material in the embodiment of the present application uses polyethylene glycol 400, which is purchased from China National Pharmaceutical Group.
[0061] A suspension printing method for enhancing material connection strength, using the support bath, the material is heated after printing to fuse the printed structure layers to enhance strength.
[0062] One or more of the gelatin and methacrylic anhydride gelatin. The material in the embodiment of the present application is methacrylic anhydride gelatin, which is purchased from Suzhou Yongqinquan Intelligent Equipment Co., Ltd.
[0063] A multi-material suspension printing method utilizes the support bath, adds a cross-linking agent inside, prints one or more materials in the support bath, and solidifies the printed structure in the support bath.
[0064] The material is one or more of sodium alginate, gelatin, methacrylic anhydride gelatin, chitosan, hyaluronic acid, and collagen. The materials in the embodiments of the present application are methacrylic anhydride gelatin purchased from Suzhou Yongqinquan Intelligent Equipment Co., Ltd., sodium alginate purchased from China National Pharmaceutical Group, and gelatin purchased from Merck, USA.
[0065] The additive is one or more of calcium chloride, transglutaminase, sodium hydroxide, and calcium hydroxide. The materials used in the examples of the present application are calcium chloride purchased from China National Pharmaceutical Group, transglutaminase purchased from Cool Chemical, and sodium hydroxide purchased from China National Pharmaceutical Group.
[0066] Example 1
[0067] In this embodiment, the proportion of each component is 2% of hydrophobic treated hydroxypropyl methylcellulose and 5% of poloxamer. The support bath material is prepared using the components in this mass proportion, and the specific steps are as follows:
[0068] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 5 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0069] S2: The completely dissolved poloxamer solution was heated to 50° C., 2 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0070] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0071] Example 2
[0072] In this embodiment, the proportion of each component is 3% of hydrophobic treated hydroxypropyl methylcellulose and 5% of poloxamer. The support bath material is prepared using the components in this mass proportion, and the specific steps are as follows:
[0073] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 5 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0074] S2: The completely dissolved poloxamer solution was heated to 50° C., 3 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0075] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s-1 , 70-150 seconds 0.01s -1 ).
[0076] Example 3
[0077] In this embodiment, the proportion of each component is 3.5% of hydrophobic treated hydroxypropyl methylcellulose and 5% of poloxamer. The support bath material is prepared using the components in this mass proportion, and the specific steps are as follows:
[0078] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 5 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0079] S2: The completely dissolved poloxamer solution was heated to 50° C., 3.5 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve the solution, thereby obtaining a supporting bath material.
[0080] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0081] Example 4
[0082] In this embodiment, the proportion of each component is 2% of hydrophobic treated hydroxypropyl methylcellulose and 10% of poloxamer. The preparation of the support bath material using the components in this mass proportion is as follows:
[0083] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 10 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0084] S2: The completely dissolved poloxamer solution was heated to 50° C., 2 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0085] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0086] Example 5
[0087] In this embodiment, the proportion of each component is 3% of hydrophobic treated hydroxypropyl methylcellulose and 10% of poloxamer. The preparation of the support bath material using the components in this mass proportion is as follows:
[0088] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 10 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0089] S2: The completely dissolved poloxamer solution was heated to 50° C., 3 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0090] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0091] Example 6
[0092] In this embodiment, the proportion of each component is 4% of hydrophobic treated hydroxypropyl methylcellulose and 10% of poloxamer. The preparation of the support bath material is carried out using the components in this mass proportion, and the specific steps are as follows:
[0093] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 10 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0094] S2: The completely dissolved poloxamer solution was heated to 50° C., 4 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve the solution, thereby obtaining a supporting bath material.
[0095] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0096] Example 7
[0097] In this embodiment, the proportion of each component is 2% of hydrophobically treated hydroxypropyl methylcellulose and 15% of poloxamer. The preparation of the support bath material using the components in this mass proportion is as follows:
[0098] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 15 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0099] S2: The completely dissolved poloxamer solution was heated to 50° C., 2 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0100] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1) .
[0101] Example 8
[0102] In this embodiment, the proportion of each component is 3% of hydrophobic treated hydroxypropyl methylcellulose and 15% of poloxamer. The support bath material is prepared using the components in this mass proportion, and the specific steps are as follows:
[0103] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 15 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0104] S2: The completely dissolved poloxamer solution was heated to 50° C., 3 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0105] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0106] Example 9
[0107] In this embodiment, the proportion of each component is 4% of hydrophobic treated hydroxypropyl methylcellulose and 15% of poloxamer. The support bath material is prepared using the components in this mass proportion, and the specific steps are as follows:
[0108] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 15 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0109] S2: The completely dissolved poloxamer solution was heated to 50° C., 4 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve the solution, thereby obtaining a supporting bath material.
[0110] The temperature-viscosity characteristics (1s -1 Shear rate), viscosity-shear rate characteristics (26°C), viscosity-time characteristics (26°C, 0-60 seconds 0.01s -1 , 60-70 seconds 10s -1 , 70-150 seconds 0.01s -1 ).
[0111] Example 10
[0112] In this embodiment, the proportion of each component is 3% of hydrophobically treated hydroxypropyl methylcellulose, 10% of poloxamer and 5% of polyethylene glycol 400. The support bath material is prepared using the components in this mass proportion, and the specific steps are as follows:
[0113] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 10 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0114] S2: Stir the completely dissolved poloxamer solution and gradually add 5 g of polyethylene glycol 400.
[0115] S3: The mixed solution of completely dissolved poloxamer and polyethylene glycol 400 was heated to 50° C., 4 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0116] The temperature-viscosity characteristics (1s -1 shear rate).
[0117] Embodiment 11
[0118] In this embodiment, the support bath ratio is 3% of hydrophobically treated hydroxypropyl methylcellulose, 10% of poloxamer, 5% of polyethylene glycol 400 as eluent, and 15% of methacrylic anhydride gelatin as ink. The support bath material is prepared using the components in this mass ratio, and the specific steps are as follows:
[0119] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 10 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0120] S2: The completely dissolved poloxamer solution was heated to 50° C., 3 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0121] S3. Weigh 100 ml of phosphate buffered saline solution into a beaker, gradually add 5 g of polyethylene glycol and stir for 20 minutes to completely dissolve it to form an eluent.
[0122] S4. Weigh 10 ml of phosphate buffered saline solution into a beaker, heat it to 40°C, gradually add 1.5 g of methacrylic anhydride gelatin and stir for 20 minutes to completely dissolve it to form ink.
[0123] S5. After printing the ink into the support bath at 28°C, put it into a water bath and heat it for 10 minutes. Curing it with light for 1.5 minutes and then take it out.
[0124] S6. In the control group, the ink was printed into the support bath at 28°C and kept at room temperature for 10 minutes. After being cured with UV light for 1.5 minutes, it was taken out and rinsed with an eluent.
[0125] The strength of the printed samples was measured using a universal tensile tester.
[0126] Example 12
[0127] In this embodiment, the support bath ratio is 3% of hydrophobically treated hydroxypropyl methylcellulose, 10% of poloxamer, 0.1% of calcium chloride, 1% of transglutaminase, the eluent is 5% of polyethylene glycol 400, the ink is 5% of methacrylic anhydride gelatin, 10% of gelatin, and 2% of sodium alginate. The support bath material is prepared using the components in this mass ratio, and the specific steps are as follows:
[0128] S1: Weigh 100 ml of phosphate buffered saline into a beaker, place it in a refrigerator to cool to 4°C, weigh 10 g of poloxamer, add it, and place it in a 4°C refrigerator overnight until it is completely melted.
[0129] S2: Stir the completely dissolved poloxamer solution, and gradually add weighed 0.1 g calcium chloride, 1 g transglutaminase, and 0.1 g sodium hydroxide to form a mixed solution.
[0130] S3: The completely dissolved mixed solution was heated to 50° C., 3 g of hydrophobically treated hydroxypropyl methylcellulose was gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a supporting bath material.
[0131] S4. Weigh 100 ml of phosphate buffered saline solution into a beaker, gradually add 5 g of polyethylene glycol and stir for 20 minutes to completely dissolve it to form an eluent.
[0132] S5. Weigh 10 ml of phosphate buffered saline solution into a beaker, heat it to 40°C, gradually add 0.5 g of methacrylic anhydride gelatin and stir for 20 minutes to completely dissolve it, forming a 5% methacrylic anhydride gelatin solution.
[0133] S6. Weigh 10 ml of phosphate buffered saline into a beaker, heat to 40°C, gradually add 0.2 g of sodium alginate and stir for 30 minutes to completely dissolve it, forming a 2% sodium alginate solution.
[0134] S7. Weigh 10 ml of phosphate buffered saline into a beaker, heat to 40°C, gradually add 1 g of gelatin and stir for 20 minutes to completely dissolve it to form a 10% gelatin solution.
[0135] S8. Print the methacrylic anhydride gelatin solution, sodium alginate solution, and gelatin solution into the support bath, cure with UV light for 1.5 minutes, place at 37°C for 6 hours, take out, and rinse with eluent.
[0136] The above descriptions are only some preferred embodiments of the present disclosure and an explanation of the technical principles used. Those skilled in the art should understand that the scope of application involved in the embodiments of the present disclosure is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above application concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present disclosure.
Claims
1. A 3D printing method, characterized in that: The 3D printing method comprises the following steps: Weighing a phosphate buffered saline solution and / or deionized water and placing them in a mixing container, then placing the mixing container in a refrigeration device to cool it to 4° C., weighing a preset mass of poloxamer and adding it to the mixing container, and maintaining the temperature of the refrigeration device at 4° C. until the poloxamer is completely dissolved; The solution after the poloxamer is completely dissolved is heated to 50° C., and a preset mass of hydrophobic-treated hydroxypropyl methylcellulose is gradually added and stirred for 20 minutes to completely dissolve it, thereby obtaining a support bath material; adding additives to the support bath material; Performing 3D printing in a mixture of the support bath material and the additive using a 3D printing material; After the 3D printing is completed, at least the support bath material is eluted using an eluting liquid.
2. The 3D printing method according to claim 1, characterized in that: The hydrophobic treatment comprises: Stearyl groups were grafted onto hydroxypropyl methylcellulose.
3. The 3D printing method according to claim 1, characterized in that: The additives include one or more of calcium chloride, transglutaminase, sodium hydroxide and calcium hydroxide.
4. The 3D printing method according to claim 1, characterized in that: The 3D printing material includes one or more of sodium alginate, gelatin, methacrylic anhydride gelatin, chitosan, hyaluronic acid, and collagen.
5. The 3D printing method according to claim 1, characterized in that: The eluent includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500, polyethylene glycol 600, and polyethylene glycol 800.
6. The 3D printing method according to claim 1, characterized in that: The mass percentage of hydroxypropyl methylcellulose in the support bath material is in the range of 2% to 4%; the mass percentage of poloxamer in the support bath material is in the range of 5% to 15%; The rest is phosphate buffer solution and / or deionized water.
7. The 3D printing method according to claim 1, characterized in that: The structural formula of the hydrophobically treated hydroxypropyl methylcellulose is: Where R is -H or -CH3 or -[CH2CH(CH3)O] m H or -CH2CH(OH)CH2OC 18 H 37 .
8. The 3D printing method according to claim 1, characterized in that: The structural formula of the poloxamer is: 。 9. A combination of a support bath and an eluent thereof, characterized in that: The mass percentage of hydroxypropyl methylcellulose in the supporting bath material is in the range of 2% to 4%; the mass percentage of poloxamer in the supporting bath material is in the range of 5% to 15%; The rest is phosphate buffer solution and / or deionized water; The eluent includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500, polyethylene glycol 600, and polyethylene glycol 800.
Citation Information
Patent Citations
Support bath materials and methods and
CN115353726A